Kualitas Hidup Pasien Penyakit Ginjal Kronik yang Menjalani Hemodialisis: Systematic Review: Quality of Life of Chronic Kidney Disease Patients Undergoing Hemodialysis: A Systematic Review - Fitri Mailani (Fakultas Keperawatan Universitas Andalas, 2015)
Quality of life is one indicator of the success of hemodialysis therapy. The purpose sistematic reviewwasto analysis the quality of life of patients chronic kidney disease undergoing hemodialysis. The method used iselectronic data base of journals published by ProQuest, CINAHL, and Springerlink. The results of a review of 15journals that have been expressed the quality of life patients chronic kidney disease who undergo hemodialysis.Instrument most widely used the Kidney Disease Quality of Life Short Form 36 (SF KDQOL 36) (n = 11). Factorsthat affect the quality of life of patients with chronic kidney disease who undergo hemodialysis are sociodemographic factors such as gender, age, education level, marital status, employment status or economic status.Other factors of depression, severity / stage renal disease, the presence of comorbidities, length of hemodialysis,does not adhere to treatment, high body mass index, social support, adequacy of hemodialysis, and interdialitycweight gain (IDWG), urine output, and hemoglobin values. Conclusion, a very important quality of life assessmentis done, and the selection of appropriate instruments will affect the quality of life assessment results are moreobjective. Collaborative team is need to increase the quality of life of patients with chronic kidney diseaseundergoing hemodialysis.